“MORPHING BOX” – AN INTERACTIVE APPLICATION FOR USE IN MUSEUMS - Feist, Manuela; Sieck, Jürgen; Witt, Michael (International Journal of Computing, 2010)
This paper presents an approach to developing a morphing application for use in museums in order to involve visitors directly in an exhibition and to increase their user experience. The visitors take an active part in generating a unique image from their own portrait and a selected reference picture. Techniques used for the development of this interactive prototype include face detection and morphing algorithms.